2016
DOI: 10.1590/2318-0331.011616055
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of physicochemical species concentration in streams based on heavy rainfall event data obtained for high-frequency monitoring

Abstract: Studies carried out over short time intervals assist in understanding the biogeochemical processes occurring relatively fast in natural waters. High frequency monitoring shows a greater variability in the water quality during and immediately after heavy rainfall events. This paper presents an assessment of the surface water quality parameters in the Atlantic Forest biome, caused by heavy rainfall events. The work was developed in two fluviometric sections of the Concordia River watershed, located in the state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Calcium ion is one of the major inorganic substances present in nearly all water systems attributable to its easy solubility from all rocks, including limestone, chalk, dolomite and gypsum (Bartram & Ballance, 1996). The values of EC and TDS were slightly varied across the months, the higher values were recorded in October 2022 which might have been influenced by the season (Girardi et al, 2016). Ewa et al (2011) in a related study reported that a high level of EC usually corresponds to a high value of TDS.…”
Section: Relationship Between Environmental Variables and The Insects...mentioning
confidence: 95%
“…Calcium ion is one of the major inorganic substances present in nearly all water systems attributable to its easy solubility from all rocks, including limestone, chalk, dolomite and gypsum (Bartram & Ballance, 1996). The values of EC and TDS were slightly varied across the months, the higher values were recorded in October 2022 which might have been influenced by the season (Girardi et al, 2016). Ewa et al (2011) in a related study reported that a high level of EC usually corresponds to a high value of TDS.…”
Section: Relationship Between Environmental Variables and The Insects...mentioning
confidence: 95%
“…As áreas urbanas onde há lançamento de efluentes domésticos sem tratamento, contribuem para o aumento da condutividade elétrica, tal qual a situação observada em P5, que está localizado na cidade de Piracuruca. Resultado semelhante foi observado por Girardi et al (2016) ao estudar a qualidade da água da bacia hidrográfica do rio Cubatão do Sul em Santa Catarina e por Mateus et al (2015) estudando a qualidade da água do rio Uberaba em Minas Gerais. Os valores elevados para condutividade elétrica em P7 situado em área rural com grande atividade de rizicultura, pode ser atribuído devido ao transporte de compostos iônicos utilizados na agricultura, tais como potássio, fósforo e nitrogênio.…”
Section: Análise Da Qualidade Da áGua Da Baciaunclassified
“…For the historical series of water quality data, several factors may influence the frequencies present in the signal, such as rainfall seasonality, intraday variations in atmospheric pressure, variations in metabolism of aquatic organisms, and even cyclic effluent discharges (CARVALHO et al, 2015;DAMASCENO et al, 2015;GIRARDI et al, 2016). Nevertheless, it is possible to verify which frequencies have the highest density in the signal, that is, which are present and which predominate in the historical series, showing which periodicities are relevant.…”
Section: Introductionmentioning
confidence: 99%